Assessment of prevalence and motivators for family planning utilisation among youth students in higher learning institutions in Dodoma, Tanzania: A cross sectional study. - Upendo Munuo; Fabiola Vincent Moshi (PLoS ONE)
Background Sub-Sahara Africa (SSA) has the greatest unmet need for family planning use, but young people are reported to under-utilise family planning services compared to other groups of women of the reproductive age in the region. Thus, promoting contraceptive services use among adolescents is vital in achieving universal access to sexual and reproductive health services. Objective The main objective of this study was to assess the prevalence and motivators for family planning services utilization among youth students in higher learning institutions in Dodoma, Tanzania. Methods An analytical cross-sectional study was conducted among 421 randomly selected youths in higher learning institutions in Dodoma. A self-administered structured questionnaire adopted from previous studies was used to collect data. Bivariate and multivariate logistic regression analysis using SPSS version 25 established association between variables. Statistical significance was declared at 95% confidence interval with α<0.05 and strength of association was reported by Odds Ratio (OR) and Adjusted Odds Ratio (AOR). Results Majority of the participants 221 (52.5%) were females, and most of them 320 (76.0%) were aged between 21 to 24 years. Of all participants, bachelor's degree scholar were 257 (61.0%). About 305, (72.4%) participants reported to have had sexual intercourse in the past 12 month. Of these 50.5% had their first intercourse at the age between 15 to 19 years. Most participants 239 (56.8%) reported to have used contraceptive method in the past 12 months. After adjusting for confounders (participants' socio-demographic characteristics), the motivators for family planning use among youth students were: living with relatives (AOR = 2.904, p 0.006), adequate FP knowledge (AOR = 2.230 p 0.003), positive perception (AOR = 1.772, p 0.025) and discussing FP matters with sexual partners (AOR = 6.045, p <0. 001). Conclusion This study highlights a significant unmet need for family planning services among youth students in higher learning institutions in Dodoma, Tanzania, reflecting broader trends in Sub-Saharan Africa. Despite high sexual activity, family planning utilization remains suboptimal. Key motivators for using family planning services include living with relatives, having adequate knowledge, positive perceptions, and discussing family planning with sexual partners. These findings emphasize the need for targeted interventions focusing on education, fostering positive perceptions, and encouraging open partner discussions to enhance family planning utilization among adolescents, contributing to universal access to sexual and reproductive health services.